A clinically managed weight loss program evaluation and the impact of COVID-19 - Cachero, Katrina; Mollard, Rebecca; Myrie, Semone; MacKay, Dylan (Frontiers in Nutrition, 2023)
With the prevalence of obesity increasing, many weight-loss programs were created to aid in combating the trend. The Weight Loss Clinic (WLC) was created to provide personalized support for lifestyle changes using a multidisciplinary team with medical oversight. This study evaluated the clinically-managed weight loss program at the Wellness Institute. Methods: This was a prospective evaluation of a newly established program between January 2019-August 2020. Participants who entered the weight loss program were approached to learn about the evaluation. A total of 41 participants were included. The primary outcomes included changes in body weight and achievement of more than 5% initial body weight loss. Outcome measures were collected pre- and post- program and the data was analyzed through paired t-tests on R studio. Results: Greater body weight-loss was seen in completers pre-COVID-19 compared to those who completed during the pandemic (Mean, +SD) (7.51+6.24 kg n=13 P < 0.001 versus 1.75+4.43 kg n=9, P = 0.02). Completers pre-COVID-19 demonstrated improvements in waist circumference, Framingham risk score, blood pressure, hemoglobin A1C, and body fat percentage. Conclusions and Implications: Though the sample size was small to show definitve evidence, the results may suggest the program worked well prior to the pandemic but the pandemic created barriers to weight-loss for participants.